1982
DOI: 10.1111/j.1399-3054.1982.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prolamellar bodies and prothylakoids fractionated from wheat etioplasts

Abstract: Prolamellar bodies and prothylakoids from etioplasts of wheat (Triticum aestivum L. cv. Starke II, Weibull) were separated by sucrose density gradient centrifugation. Top‐loaded and bottom‐loaded sucrose gradients were compared. As a consequence of avoiding long time exposure of the membranes to low sucrose concentrations, separation in bottom‐loaded gradients, as compared to separation in top‐loaded gradients, resulted in a sharper and more narrow band of prothylakoids, and in better preservation of phototran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 29 publications
6
111
0
Order By: Relevance
“…Previous studies on the effects of FR irradiation on plastid structure have revealed that this treatment leads to a deficiency in the ordered membrane system of the prolamellar body (Oelmü ller et al, 1986;Barnes et al, 1996;Sperling et al, 1997). This can be largely attributed to the dramatic decline in PORA (Runge et al, 1996), which is the major protein component of the prolamellar body (Ryberg and Sundqvist, 1982;Ikeuchi and Murakami, 1983). In addition, the development of vesicles, which may be related to degradation of plastid components, has also been observed (Barnes et al, 1996).…”
Section: The Transcriptionally Coupled Response Results In the Loss Omentioning
confidence: 95%
“…Previous studies on the effects of FR irradiation on plastid structure have revealed that this treatment leads to a deficiency in the ordered membrane system of the prolamellar body (Oelmü ller et al, 1986;Barnes et al, 1996;Sperling et al, 1997). This can be largely attributed to the dramatic decline in PORA (Runge et al, 1996), which is the major protein component of the prolamellar body (Ryberg and Sundqvist, 1982;Ikeuchi and Murakami, 1983). In addition, the development of vesicles, which may be related to degradation of plastid components, has also been observed (Barnes et al, 1996).…”
Section: The Transcriptionally Coupled Response Results In the Loss Omentioning
confidence: 95%
“…Protein Analyses-Three different methods were employed to prepare and analyze POR-pigment complexes, that of Ryberg and Sundqvist (26), that of Klement et al (27), and a modified version of that of Gerhardt and Heldt (28).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that glycolipid composition of PLB and PT fractions was qualitatively similar (22). Ryberg and Sundqvist (21) and Ikeuchi and Murakami (10) showed that PT fractions contained several polypeptides while the PLB fraction was dominated by one polypeptide. The methods used in these studies (10,21,22) for separating PLBs and PTs resulted in pure PLB fractions whereas the PT fractions probably contained PLB fragments and/or envelope membranes.…”
mentioning
confidence: 99%